Cornell-Based Insights: Analyzing Farmers’ Attitudes towards Scientific Backyard Poultry Farming Using the Guttman Scale - Choudhary, Khushboo; Shruti,; Singh, Madan; Verma, Harideep (Indian Journal of Extension Education, 2025)
The study focused on developing a Guttman Scale using the Cornell technique of the scalogram approach to assess farmers' attitudes towards scientific backyard poultry farming. While the Likert-type summated rating scale is commonly used in social science research, this paper explained the application of the Guttman scale. Out of 70 items selected, 55 statements were analysed, with 42 retained after ensuring a reproducibility coefficient of 0.85 or higher. The final scale demonstrated a high reproducibility coefficient of 0.92, reflecting strong accuracy in measuring the attitude of farmers towards scientific poultry farming. The scale's reliability and validity were confirmed through the split-half method, Cronbach's alpha, and content validity assessments. The final scale can be administered using a five-point continuum, ranging from highly unfavourable to highly favourable. This tool offers a valuable platform for assessing farmers' attitudes towards scientific backyard poultry farming. Following the scalogram approach, this cumulative scale will also serve as a useful reference for researchers in the social sciences seeking to develop similar measurement tools.